A sol–gel approach to produce highly dispersed graphene oxide–carbon nanotube hybrid reinforcement into alumina matrix. (4th April 2017) - Yazdani Damavandi, Bahareh; Xia, Yongde; Ahmad, Iftikhar; Zhu, Yanqiu
Abstract: In this article, a hybrid of graphene oxide (GO) and carbon nanotube (CNT) (GONT) was used as the reinforcement to prepare Al2 O3 –rGONT nanocomposites. Hot pressing was used to fabricate the nanocomposites, which promoted in situ GO reduction and ceramic matrix sintering at the same time. The effects of various GO/CNT ratio combinations on the structural features and mechanical properties of the nanocomposites have been investigated and toughening mechanisms have been analysed. By adopting a new sol–gel approach, in addition to the direct powder mixing, it has been found that the sol–gel process leads to an impressive grain size reduction of 62%, and the fracture toughness and flexural strength reached 6.2 MPa·m 1/2 and 420 MPa (i.e. 70% and 14% improvement), respectively, benchmarked against those of pure Al2 O3, which even marginally outperformed our previously optimised Al2 O3 nanocomposites reinforced by the blend of graphene platelets and CNTs. The success of our new sol–gel strategy opens up new opportunities for choosing hybrid reinforcements for the fabrication of advanced ceramic nanocomposites.